Keandalan Komponen Nose Wheel Assy pada Pesawat Cessna - Sri Mulyani; Istyawan Priyahapsara (Universitas Muhammadiyah Yogyakarta, 2023)
Maintenance is taken to maintain the reliability of the components that support overall nurse performance. One of them is the landing gear which functions for all aircraft movements on the ground including taking off, landing, taxing and parking, and holding the aircraft's load while on land. Nose wheel assy is provided to hold the nose of the aircraft and maneuver while on the ground. Based on information obtained from the engineering department as well as looking at the maintenance logbook on the ATR 72-500 aircraft there was a problem with the nose wheel assy. Where these problems can result in the movement of the aircraft will be problematic. The method used is the Weibull distribution analysis method, the main objective is to determine the failure rate and the reliability of these components as well as to determine the characteristics of the failure modes caused. The parameters used in this distribution are the shape parameter (β) and the scale parameter (h). From the calculation analysis results, it can be seen that the nose wheel assy component based on time failure will function until it fails at the age of 585 hours 38 minutes and β is 3.513864. Following the provisions that apply to values β 1,the type of failure that occurs is a type of failure to wear out. While based on the cycle will function until experiencing failure at the age of 398 hours 13 minutes and β is 1.258549 Under the provisions that apply to values β 1, type failure that occurs is a type of wear out. This type of failure has the property of increasing the failure rate with increasing use, therefore for nose wheel, assy components more effective preventive maintenance is applied.This type of failure has the property of increasing the failure rate with increasing use, therefore for landing gear, assy components more effective preventive maintenance is applied.